Structural and functional characterisation of a novel bovine β-defensin gene cluster - Narciandi Martin, Fernando (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2013)
Antimicrobial peptides (AMPs) have been characterised by their ability to neutralise pathogens directly by disrupting their membranes. Recently described roles for these peptides include chemotactic activity, wound healing and regulation of the inflammatory response. AMPs have also been shown to have non-immune functions, such as control of coat colour and roles in embryonic development, sperm maturation and fertility. Using combined bioinformatics and molecular approaches, our group found a new cluster of p-defensin genes in the bovine genome on chromosome 13. Expression of the gene cluster was exclusive to the reproductive tract with little or no expression in any other tissue. The aims of this study are to further investigate this cluster of genes, to characterise their expression, to examine their genetic variability, population structure and to explore a possible role in fertility. We also set out to create the tools required for their functional characterisation.
Keywords: Biochemistry & Immunology, Ph.D.; Ph.D. Trinity College Dublin.